1995
DOI: 10.1016/s0266-7681(05)80056-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Complications in Endoscopic Carpal Tunnel Release

Abstract: Single portal endoscopic carpal tunnel release was carried out in 107 hands of 88 patients. There were 11 complications. These included incomplete release (2), post operative scarring around the median and ulnar nerves (2), laceration of the superficial palmar arterial arch (1), reflex sympathetic dystrophy (2), palmar fasciitis (1), and wound inflammation (3). In two cases there was no relief of symptoms. In one there was incorrect diagnosis and in another, incorrect indication for endoscopic carpal tunnel re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1
6

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 17 publications
2
25
1
6
Order By: Relevance
“…We found an incidence of 6.6% for CRPS following the CTR surgery, which was comparable to the results of previous reports (6).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We found an incidence of 6.6% for CRPS following the CTR surgery, which was comparable to the results of previous reports (6).…”
Section: Discussionsupporting
confidence: 91%
“…Da Costa et al reported an incidence of 8.3 % for CRPS following the CTR surgery (15), which was higher than the incidences reported earlier (2.1% to 5%) (6). We found an incidence of 6.6% for CRPS following the CTR surgery, which was comparable to the results of previous reports (6).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…These complications range from simple incomplete release of the transverse carpal ligament to injuries to the superficial palmar arterial arch, from transection of the ulnar artery to persistent sensory disturbances of individual digital nerves, severe scarring around the median and ulnar nerves, partial injuries to and complete transections of either nerve [2,8,12,13,14,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…By measuring the pressure throughout the carpal tunnel during the ECTR, sufficient decompression can be achieved and incomplete release avoided [2,17]. We can also prevent excessive release leading to neurovascular injury [20]. In this study, we performed ECTR with simultaneous measurement of the carpal tunnel pressure using the original method in HD-CTS and in I-CTS.…”
Section: Introductionmentioning
confidence: 99%